O gênero oral debate em sala de aula: um estudo de caso - Gonçalves, Luciana Fabíola (2009)
Oral genres integrate one of the directives proposed by Portuguese PCNs. However, many teachers face great difficulty in dealing with it. Oral genres seem to have been considered a secondary teaching practice in Brazilian schools. There are few theoretical references to the development of pedagogic practices that utilize this genre. In order to improve teaching using oral genres, this study analyzed a classroom debate with sixth grade students during a Portuguese language class, presenting a didactic sequence for the teaching of this gender. Our aim was to analyze student interaction during the debate and which linguistic elements were used by the students and by the teacher-moderator. This work is based on socio-interactive speech (BAKHTIN, 2002; BRONCKART, 1999, 2007); interaction through language (KOCH, 2000); oral and written characteristics (MARCUSHI, 2007a); the importance of oral genres in the classroom and the development of didactic sequences (DOLZ & SCHNEUWLY, 2004a, 2004b; DOLZ, NOVERRAZ & SCHNEUWLY, 2004; the characteristics of classroom debates (RIBEIRO, 2009). This study showed that, generally, elementary school teachers face difficulty in using oral genres in the classroom. We concluded that the students were not being correctly oriented to interact in this genre, because they could not explore adequately the linguistic elements that lead to a more comprehensive interaction. The teacher would have had better results have if he would have started from a didactic sequence